Pendampingan Pembuatan Narasi Sejarah dan Kebudayaan Kerajaan Adat Marusu Melalui Teknologi Tepat Guna [Assistance in Developing Historical and Cultural Narratives of the Marusu Customary Kingdom through Appropriate Technology] - Fajar Sidiq Limola; A Lili Evita; Muhammad Ridha Anugrah; Indo Alang; Nizar Ckholifa; Andi Usrawi Maappaseng; Elsa Stefhanie Saung (UKInstitute, 2026)
This Community Service activity is motivated by the absence of a systematic historical and cultural narrative in the area of the Marusu Customary Kingdom, located in Baju Bodoa Subdistrict, Maros Baru District, Maros Regency, as well as the partners’ limited capacity in using cultural documentation technology. The purpose of this activity is to assist the local community in compiling historical and cultural narratives through a participatory approach and training in the use of appropriate digital technology. The methods used include stages of historical research—heuristics, verification, interpretation, and historiography—combined with audio-visual documentation training. The activity involved traditional leaders, cultural maestros, and youth in the processes of interviews, visual documentation, and narrative validation. The outcomes include an online-published documentary video on the history and culture of the Marusu Customary Kingdom and a pocket book containing historical narratives based on oral sources. This activity has enhanced the partners’ capacity in managing digital media and strengthened collective awareness of the importance of preserving local history and culture. The program demonstrates the effectiveness of community-based collaboration in cultural preservation and is recommended for replication in other customary regions to reinforce local identity. Abstrak. Kegiatan Pengabdian kepada Masyarakat ini dilatarbelakangi oleh belum adanya narasi sejarah dan kebudayaan yang sistematis di wilayah Kerajaan Adat Marusu, Kelurahan Baju Bodoa, Kecamatan Maros Baru, Kabupaten Maros, serta keterbatasan mitra dalam penguasaan teknologi dokumentasi budaya. Tujuan kegiatan ini adalah mendampingi masyarakat lokal dalam menyusun narasi sejarah dan budaya melalui pendekatan partisipatif serta pelatihan penggunaan teknologi digital yang tepat guna. Metode yang digunakan mencakup tahapan penelitian sejarah meliputi heuristik, verifikasi, interpretasi, dan historiografi, dikombinasikan dengan pelatihan dokumentasi audio-visual. Kegiatan ini melibatkan tokoh adat, maestro budaya, dan pemuda dalam proses wawancara, dokumentasi visual, dan validasi narasi. Hasil kegiatan meliputi video dokumenter sejarah dan budaya Kerajaan Adat Marusu yang dipublikasikan secara daring serta buku saku berisi narasi sejarah berbasis sumber lisan. Kegiatan ini meningkatkan kapasitas mitra dalam pengelolaan media digital serta memperkuat kesadaran kolektif terhadap pentingnya pelestarian sejarah dan budaya lokal. Program ini membuktikan efektivitas kolaborasi berbasis komunitas dalam pelestarian budaya dan direkomendasikan untuk direplikasi di wilayah adat lainnya guna memperkuat identitas lokal.